(untitled) (Al-Qamar, 2022)
Allāma Saeedī was a versatile personality in the field of Islamic sciences. He was simultaneously an authentic scholar, a rare writer, a great hadith scholar, an unparalleled orator, an excellent teacher, a broad-minded jurist, a mature historian, a master of literature, logic and philosophy. He was an expert in education and teaching, and was a comprehensive, reasonable and personable personality. All his writings are full of scientific and jurisprudential research. One of these works is the commentary "Tibayān al-Qurān" in which Allāma Sāhib has presented hundreds of hadith interpretations and a summary of the Qurān, This Tafsīr consists of twelve thick volumes and about twelve thousand pages, this Tafsīr is a great scholarly and jurisprudential encyclopedia of ancient and modern research. Especially, the best and correct solution to the complex and precise problems of the present age has been presented. In this article, a brief overview of the format, style and features of this commentary is presented.